Effect of Yoga on obesity, hypertension and lipid profile - Gadham, Jayaram; Sajja, Srikanth; Rooha, V. (International Journal of Research in Medical Sciences, 2017)
Background: Hypertension is a major chronic lifestyle disease and an important public health problem worldwide. Mind-body therapies i.e., the transcendental meditation and Yoga have raised interest as they represent an alternative to medication; also contribute to an increased feeling of empowerment for patients in preventing and treating hypertension. Yoga, as a therapeutic regimen, has been shown to be useful to individuals with cardiovascular diseases and diabetes. The objective of our study is to study the effect of Pranayama and certain Yogic Asana’s on BP, BMI & lipid profile. Methods: 50 male subjects in the age group of 35-55 years were randomly selected based on exclusion criteria. BP, BMI and lipid profile was estimated before any intervention. They were subjected to pranayama and other Asana’s for a period of 3 months. After 3 months of Yoga intervention, BP, BMI and lipid profile was estimated. Results: We observed a statistically significant decrease in Systolic BP, Diastolic BP and BMI after 3 months of Yoga training. Also, we observed a decrease in total cholesterol, VLDL, triglycerides and an increase in HDL cholesterol which is not statistically significant. Conclusion: A significant decrease in systolic blood pressure and diastolic blood pressure in subjects who have practiced Yoga, Asanas along with pranayama technique for 3 months duration.